Pharmacokinetics of fructose-1,6-diphosphate after intraperitoneal and oral administration to adult rats - Xu, Kaiping (2008)
Exogenously administered fructose-1,6-diphosphate (FDP) has been studied for its ability to protect tissue during hypoxia or ischemia. Recently, a clear effect of FDP on the central nervous system has raised the question whether FDP can get into the brain. FDP levels were measured in blood, brain, liver, kidney, muscle and fat after intraperitoneal administration of a single 0.5g kg-1 dose of FDP to adult male Sprague-Dawley rats. A complete time course of the levels in blood and brain was determined. The levels of FDP in the blood and brain increase simultaneously, i.e. there is no lag in the increase in the brain. The levels of FDP fall to baseline in liver, kidney, muscle and fat by 12 hours, but remain elevated in blood and brain. However, levels in the blood at 12 hours are significantly decreased from the peak levels, while those in brain are not different from the peak levels, suggesting that the kinetics of FDP in blood and brain are quite different. Stripping the endothelial cells from the brain tissue sample did not change the levels of FDP indicating that FDP is not trapped in the capillary cells. Incubation of brain slices in a solution of FDP, followed by washing, raised tissue levels of FDP indicating that FDP is taken up into cells within the brain. Finally, the experiments demonstrate a significant increase in brain levels of FDP after oral administration. These data suggest that an oral formulation of FDP might be developed for treatment of neurological disease.